158 Comparison of Cost and Complication Rates for Profiling Hospital Performance in Lumbar Fusion for Spondylolisthesis. (1st April 2022) - Greenberg, Jacob K.; Olsen, Margaret; Dibble, Christopher; Zhang, Justin; Pennicooke, Brenton Henry; Yamaguchi, Ken; Kelly, Michael; Hall, Bruce; Ray, Zack
Abstract : INTRODUCTION: Despite growing interest among payers in profiling both the cost and safety of common surgeries, such as lumbar fusion, there is sparse evidence describing the statistical reliability of such measures when applied to lumbar fusion for spondylolisthesis. METHODS: We used State Inpatient Databases from nine states to study patients undergoing lumbar fusion for spondylolisthesis from 2010-2017. The study outcome was the statistical reliability of three distinct quality/value metrics. Statistical reliability was measured as the amount of variation between hospitals relative to the total amount of variation for each measure. Total variation includes both between-hospital variation ("signal") and within-hospital variation ("statistical noise"). Thus, reliability equals signal over (signal plus noise) and ranges from 0-1. We evaluated the reliability of each measure by study year and examined the number of hospitals meeting different thresholds of reliability. RESULTS: We included 66, 571 elective lumbar fusion surgeries performed at 244 hospitals. 12.0% of patients experienced a complication within 90 days of surgery, including 7.8% with a serious complication. The median reliability of 90-day cost ranged from 0.97-0.99 across study years. By comparison, the median reliability for the overall complication metric ranged from 0.22-0.44, and the reliability of the serious complication measure ranged from 0.30-0.49 across the study years. While some low-volume hospitals had reliabilities for cost as low as 0.51, at least 96% of hospitals had high (>0.7) reliability for cost in any year. By comparison, the reliability of the overall and serious complication rate varied substantially by hospital case volume, and only 0-9% and 0-11% of hospitals had high (>0.7) reliability in any year. CONCLUSION: 90-day inpatient costs following lumbar fusion for spondylolisthesis are highly reliable for assessing variation across hospitals, whereas overall and serious complications are only moderately reliable for profiling performance.